RANCANG BANGUN SISTEM INFORMASI INVENTARIS PERALATAN TEKNOLOGI INFORMASI DI SWISSBEL HOTEL DANUM PALANGKARAYA - Jadiaman Parhusip; Sherly Christina; Triastuti Prabasari (Universitas Palangka Raya, 2017)
Department Civil Engineering Faculty of Engineering, University of Palangka Raya hasfacilities and infrastructure that is often used to support the learning process. To managementinfrastructure information, Department Civil Engineering, Faculty of Engineering University ofPalangka Raya still do not have a system that can convey information about the facilities andinfrastructure to civil engineering student and other parties. To get information aboutinfrastructure, the student must meet the manager of facilities and infrastructure.Website inventory of facilities and infrastructures is a web based program that is designedto be able to convey information about the facilities and infrastructure in Department CivilEngineering Faculty of Engineering, University of Palangka Raya. Some images on this website aredisplayed with three-dimension (3D), where designed with Sketchup and 3dsMax application. Thiswebsite builded with data collection method, there are Observation, Field Studies and LibraryStudies, while the development methodology is Luther’s method. This Website using programminglanguage, there are PHP and HTML, and MySQL for database.Website inventory of facilities and infrastructures tested by blackbox testing, where theresults of testing all the systems can function to manage information about facilites andinfrastructure. For further development is expected to make improvements on features, such asimprovement in the appearance of 3D objects that can be display virtually.